A Medieval Yakut Burial Near Lake Atlasovskoye of the 14th–15th Centuries: An Anthropological Study - A. N. Bagashev; D. I. Razhev; A. V. Zubova; R. I. Bravina; V. M. Dyakonov; A. D. Stepanov; Y. V. Kuzmin; G.W. L. Hodgins; А. Н. Багашёв; Д. И. Ражев; А. В. Зубова; Р. И. Бравина; et al. (IAET SB RAS, 2016)
The burial near Lake Atlasovskoye, Yakutia, is one of the earliest Yakut burials, dating back to the 14th or 15th centuries and associated with the medieval Kulun-Atakh culture. Initially, its age was assessed by the comparative typological method based on artifacts, and later а radiocarbon estimate was generated, suggesting that the burial dates to the early stage of the Kulun-Atakh culture. Its highly unusual feature is that the individual was buried in a seated position – an exceptional case in the Yakut funerary practice. The cranium was completely wrapped in a bandage sewn from birchbark sheets, under which lethal injuries were found. Our comprehensive study was aimed at assessing the individual’s lifestyle and cause of death. Postcranial bones revealed pathologal symptoms unusual for an early age (20–25) and caused by excessive physical strain, suggesting that the man was either a slave or a warrior. The complex birchbark bandage may indicate high status. Together with the seated position of the body, this makes the military status even more likely. Multiple traumatic lesions inflicted with a cutting tool indicate the violent nature of conflicts at the early stage of the Yakut culture. Craniometruic analysis reveals Buryat and Mongol affi nities, supporting epic evidence relating to Yakut origins, in which Buryat or Mongol immigrants had taken part.